Comparison of physiological strain and muscular performance of athletes during two intermittent running exercises at the velocity associated with VO2max - Vuorimaa, T.; Vasankari T.; Rusko, H. (International Journal of Sports Medicine, 2000)
The purpose of this study was to examine physiological strain and muscular performance responses of well trained athletes during two intermittent running exercise protocols at the velocity associated with VO2max. Ten national level middle-distance runners (VO2max 69.4+/-5.1; mean+/-SD) performed in random order two 28 min treadmill running exercises: 14 bouts of 60 s runs with 60 s rest (IR60) and 7 bouts of 120 s runs with 120 s rest between each run (IR120). During IR120 peak oxygen uptake (12%), peak heart rate (3%) and peak blood lactate (79%) were significantly higher than during IR60 (P< 0.001) and almost the same as in the VO2max test. In IR120 the relative aerobic energy release calculated on the basis of the accumulated oxygen deficit during the running bouts was significantly higher than in IR60 (81.5+/-2.7 vs. 70.2+/-2.6%, P<0.001) likewise the sum oxygen consumption during the 14 min running (P< 0.001), while during the 14 min recovery it was as much lower (P < 0.001). There were no changes either during or between the IR60 and IR120 protocols with regard to the muscular performance parameters, stride length or height of maximal vertical jumps. In conclusion, during intermittent running at the velocity associated with VO2max doubling the duration of work and rest bouts from 60 s to 120s increased the physiological strain of well trained athletes to the same level as at exhaustion in the VO2max test but the muscular performance variables were not influenced